Faktor yang Mempengaruhi Return Saham dengan Harga Saham sebagai Variabel Moderasi (Studi Kasus pada Perusahan Perbankan yang Terdaftar di BEI) - Thomas Sumarsan Goh; Henry Henry; Syawaluddin Syawaluddin; Erika Erika; Albert Albert (Politeknik Ganesha Medan, 2022)
This study aims to know the factors that impact stock return with Market Price as the moderating variable of the banking company listed on the IDX from 2015 to 2020. The data is retrieved from idx.co.id. The population of this article is 43 banking companies, and to select the sample for this article has used purposive sampling and has selected 11 companies. The analysis method of this article has used descriptive statistics. The data has gone through BLUE (best linear unbiased estimator) test, such as normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test before doing the hypothesis test. Further, the analysis data has used F-test, t-test, the equation of multiple linear regression, determination coefficient, and moderation. The study's findings are that, partially, LDR does not affect SR, ROA does not affect SR, and BOPO does not affect SR. PBV can not moderate the effect of LDR, ROA, and BOPO on stock return. The determination coefficient is 0.048 (4.8%), which means that the LDR, ROA, and BOPO have impacted SR as much as 4.8%, and the remaining is affected by other factors. The contribution of the research is to help the investors select the right stock.